Dietary fat and breast cancer: comparison of results from food diaries and food-frequency questionnaires in the UK Dietary Cohort Consortium. - Key, T; Appleby, P; Cairns, B; Luben, R; Dahm, C; Akbaraly, T; Brunner, E; Burley, V; Cade, J; Greenwood, D; Stephen, A; Mishra, G; et al. (2011)
BACKGROUND: Epidemiologic studies of dietary fat and breast cancer risk are inconsistent, and it has been suggested that a true relation may have been obscured by the imprecise measurement of fat intake. OBJECTIVE: We examined associations of fat with breast cancer risk by using estimates of fat intake from food diaries and food-frequency questionnaires (FFQs) pooled from 4 prospective studies in the United Kingdom. DESIGN: A total of 657 cases of breast cancer in premenopausal and postmenopausal women were matched on study, age, and recruitment date with 1911 control subjects. Nutrient intakes were estimated from food diaries and FFQs. Conditional logistic regression was used to estimate ORs for breast cancer associated with total, saturated, monounsaturated, and polyunsaturated fat intakes with adjustment for relevant covariates. RESULTS: Neither the food diaries nor the FFQs showed any positive associations between fat intake and overall breast cancer risk. ORs (95% CIs) for the highest compared with lowest quintiles of percentage of energy from total fat were 0.90 (0.66, 1.23) for food diaries and 0.80 (0.59, 1.09) for FFQs. CONCLUSION: In this study, breast cancer risk was not associated with fat intake in middle-aged women in the United Kingdom, irrespective of whether diet was measured by food diaries or by FFQs.